(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Plants are widely used for various medicinal purposes without careful consideration of potential adverse effects on the system. The fruit of Azanza garckeana is eaten as food, while the other parts are shown to have different medicinal uses and serve as treatments in managing several diseases and ailments throughout its geographical coverage. The study is a necessary/relevant addition in the ongoing efforts to increase awareness about the potential dangers of Azanza garckeana that is presently in use for multiple purposes without prior toxicity studies. Objectives: This study aimed to determine the sub-acute toxicity of the methanol root bark extract of A. garckeana (MEAG). Methods: The Organization for Economic Co-operation and Development (OECD) test guidelines (TG) 425 and 407 were followed for conducting acute oral toxicity and sub-acute toxicity study of MEAG, respectively. Results: In the overall acute toxicity test carried out on MEAG, there were no observed signs and symptoms of toxicity, morbidity or mortality and the LD50 was estimated to be greater than 5000 mg/kg in the oral route of administration. Sub-acute toxicity study, revealed a significant increase (p<0.05) in direct (conjugated) bilirubin at 400 and 800 mg/kg as well as in serum urea at 200 and 400 mg/kg in the MEAG treated groups respectively when compared to the control group. Also, histology of the rats’ organs such as liver, kidney, brain and the heart revealed some level of tissue damage such as, moderate hepatic and slight periportal necrosis, slight glomerular necrosis, as well as slight neuronal necrosis and slight myocardial necrosis, respectively. Conclusion: Prolonged administration of methanol root bark extract of Azanza garckeana appears to be toxic to Wistar rats.